Quantum dot light emitting diode device with patterned barrier layer structure
By using nanoparticle material and ligand exchange technology with approximate quantum dot particle size in nanoimprinted patterned QLED barrier layer, the problem of low barrier pickup rate and difficult to achieve crosstalk and conformal coating is solved, and efficient patterning and performance improvement is achieved.
Patent Information
- Application Number
- CN202311351292.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-10-18
AI Technical Summary
The existing nanoimprinted patterned QLED barrier layers have problems with low pickup rates, crosstalk between cells and difficulty in achieving conformal coatings, and known solutions are difficult to take into account the needs of these problems.
Nanoparticle materials with a size similar to the size of quantum dots are used to modify the barrier layer material through ligand exchange technology, so that it achieves a high pick-up rate in nanoimprinting technology, and is well wet with the quantum dot solution to form a conformal layer.
The pick-up rate and patterning quality of the barrier layer are improved, the crosstalk between cells is reduced, the formation of a conformal coating is achieved, and the overall performance of QLED devices is improved.
Smart Images

Figure CN119894229A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electroluminescent devices, and in particular relates to a quantum dot light emitting diode device with a patterned barrier layer structure. Background Art
[0002] Quantum dot electroluminescence (such as quantum dot light-emitting diodes, QLEDs) takes into account the excellent luminescence performance of colloidal quantum dots, the advantages of self-luminescence technology and solution preparation compatibility, and is one of the important candidate technologies in the field of new displays. However, quantum dot patterning technology, which directly meets the needs of industrialization, has encountered technical bottlenecks in improving patterning quality, preserving pixel luminescence efficiency, and reducing pixel size. Nanoimprinting is one of the effective means to achieve micro-nano level luminescent quantum dot film patterning.
[0003] Leakage current and crosstalk problems mainly arise from the direct contact between the electron and hole transport layers in the non-pixel region within the plane of the light-emitting layer. To reduce leakage current, it is necessary to construct a barrier layer in the non-pixel region of the light-emitting layer so that the barrier layer material and the colloidal quantum dot material form a complementary pattern within the plane of the light-emitting layer.
[0004] Nanoimprinting is a reliable technology for constructing micro-nano patterns of quantum dot films. Selecting the right barrier material plays a key role in achieving high pixel density QLED arrays through nanoimprinting technology.
[0005] At present, the materials that have been used for thin film transfer to prepare patterned barrier layers include:
[0006] 1. Polymer materials
[0007] Some polymer materials are sensitive to light or heat, which enables them to have certain patterning properties, such as PPC (polypropylene carbonate) or PMMA, etc. Patterning is achieved through nanoimprinting, and the insulation properties are good, which can meet the requirements of the barrier layer.
[0008] 2. Blue light colloidal quantum dots
[0009] As a type of quantum dot luminescent material, blue light colloidal quantum dots themselves have a large band gap and their surface is generally covered with long-chain oily ligands with good insulation properties, making them useful for preparing patterned barrier layers for some quantum dot light-emitting devices.
[0010] 3. Metal oxides
[0011] Metal oxides are commonly found in dielectric layer materials in integrated circuits, such as AI2O3, HfO2, Ta2O5, ZrO2, etc. They do not generate electroluminescence themselves and have both stability and high insulation properties. Summary of the invention
[0012] At present, the above-mentioned barrier layer materials have the following deficiencies:
[0013] Existing technology 1, barrier layer based on polymer materials: The long polymer chain structure makes it difficult to completely peel off the pixel definition area through common nanoimprint technology. Therefore, the pick-up rate of common stamps for polymer materials is very low, and the patterning integrity and quality of polymer materials at the micro-nano scale are poor.
[0014] Existing technology 2, blocking layer based on blue light colloidal quantum dots: commonly used stamps have a high pickup rate. However, on the one hand, its narrow energy band gap easily causes the blocking layer to emit light itself; on the other hand, it cannot play a charge blocking role for wide band gap luminescent pixels (such as blue light pixels), causing crosstalk between pixels.
[0015] Prior art 3, barrier layer based on metal oxide: As a barrier layer, it does not emit light itself, thus avoiding the problem of crosstalk between pixels. However, its surface is usually hydrophilic. This results in poor wettability of colloidal quantum dots (with lipophilic ligands on the surface) dispersed in a non-polar solvent on its hydrophilic surface when preparing a patterned light-emitting layer, making it difficult to achieve conformal coating of the light-emitting quantum dots by spin coating, and prone to defects.
[0016] In summary, low pick-up rate, pixel crosstalk, and difficulty in achieving conformal coating are the main difficulties of existing nanoimprint patterned QLED barrier layers. And it is difficult for the known solutions to address these problems at the same time.
[0017] In view of the defects of the current nanoimprint patterned QLED barrier layer, the present invention proposes a method for preparing a barrier layer material with high pickup rate, high insulation and good wetting with quantum dots to form a conformal layer.
[0018] In order to solve the problem of low film pickup rate of polymer materials in nanoimprinting in the prior art 1, the present invention proposes to use nanoparticle materials with a size similar to the particle size of quantum dots. This material can be effectively compatible with the existing nanoimprinting technology to achieve a high pickup rate for thin film patterns.
[0019] In order to solve the problem of self-luminescence of the blue light colloidal quantum dot barrier layer and crosstalk between pixels in the prior art 2, the present invention adopts an insulator material with a larger optical band gap and no electroluminescence property in the visible band to avoid the occurrence of self-luminescence of the barrier layer and crosstalk between pixels;
[0020] In order to solve the problem in prior art 3 that the metal oxide barrier layer has poor wettability with the quantum dot solution and cannot form a conformal coating, the present invention aims to solve technical problem 3: using ligand exchange technology to enable the barrier layer surface to achieve good wettability with the quantum dot solution to prepare a dense patterned coating with conformal contact;
[0021] In view of the defects of the existing technology, the present invention proposes a new scheme for preparing a barrier layer for quantum dot micro-nano pixel arrays based on the modification of patterned barrier layer structural materials. This scheme is compatible with most of the current nanoimprint patterning technologies and solution-based device processes. By exchanging ligands of oxide nanoparticle materials, its process performance in nanoimprint thin film patterning is improved, and a conformal coating that is well wetted with quantum dots is formed, thereby reducing pixel crosstalk and achieving the effect of improving the performance of patterned QLED devices.
[0022] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:
[0023] The present invention provides a quantum dot light-emitting diode device with a patterned barrier layer structure, comprising a device anode, a hole injection layer, a hole transport layer, a composite layer, an electron transport layer and a device cathode arranged in sequence;
[0024] The composite layer is composed of a patterned barrier layer and a light-emitting layer; the light-emitting layer is filled in the pattern gaps of the barrier layer in the form of a pixel array;
[0025] The material of the light-emitting layer is selected from one or more of II-VI quantum materials, III-V quantum materials, perovskite semiconductor materials and single-mass quantum dot materials;
[0026] The barrier layer is obtained by transferring a barrier material, and the barrier material is prepared by a solid phase modification or ligand exchange method;
[0027] The solid phase modification method is to apply the isopropanol dispersion containing the oxide on the reaction silicon wafer, add perfluorotrimethoxysilane to soak for 20-40 seconds and then dry; the ligand exchange method is to mix the isopropanol dispersion containing the oxide and the ligand for 5-7 hours and then separate, disperse the separated precipitate in n-hexane and then apply it on the reaction silicon wafer; the oxide is selected from inorganic non-metallic oxides and metal oxides; the inorganic non-metallic oxide is SiO2 nanoparticles, and the metal oxide is nanoparticles selected from HfO2, Al2O3, Ta2O5 or ZrO2; the ligand is selected from one or more of oleic acid, oleylamine, silane and octadecyl mercaptan;
[0028] The reaction silicon wafer is obtained by placing the silicon wafer and alkylsilane in hexane under a protective atmosphere, reacting for 1-2 hours, and then baking at 110-130° C. for 15-25 minutes.
[0029] Preferably, the light-emitting layer is obtained by coating the gaps in the patterned barrier layer and then annealing at 75-85°C.
[0030] The present invention introduces a quantum dot light-emitting diode device with a patterned barrier layer structure, and the preparation process is as follows: Figure 1 shown.
[0031] The gray blocks in the figure are blocking layers. In A, a pre-filmed blocking layer is spin-coated on a silicon substrate after self-assembly hydrophobic treatment; in B, a patterned film of the pre-filmed blocking layer material on the silicon substrate is picked up by a polydimethylsiloxane (PDMS) elastomer stamp; in C, the stamp with the blocking layer pattern is aligned with the corresponding area of the device electrode for film transfer and release, forming a device stack with a patterned blocking layer covered on the hole transport layer in D; in E, quantum dots (QD) are further spin-coated on it to fill the pores of the blocking layer to form a quantum dot light-emitting pixel array; the final device structure is shown in F, which includes, from bottom to top, a device anode, a hole injection layer, a hole transport layer, a patterned quantum dot light-emitting pixel array & a blocking layer forming a complementary pattern with the quantum dot pixel, an electron transport layer, and a device cathode.
[0032] The device's anode has good conductivity and can be used to transport charges.
[0033] Preferably, the thickness of the device anode is 20-200 nm, and the material is selected from one or more of indium tin oxide (ITO), fluorine-doped tin dioxide (FTO), aluminum (Al) and silver (Ag).
[0034] Hole injection layer (HIL), characterized by being solution-coated, having a work function of more than 5.1 eV and a film conductivity greater than 10 -5 S / cm.
[0035] Preferably, the hole injection layer has a thickness of 10-150 nm, and the material is selected from one or both of polyethylene polymers and polythiophene polymers.
[0036] Furthermore, the polyethylene polymer is selected from poly(thiophene-3-[2-(2-methoxyethoxy)ethoxy]-2,5-diyl)( OC), poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) and one or more of a PEDOT:PSS modified material doped with perfluoroionomer (PEDOT:PSS:PFI).
[0037] Furthermore, the polythiophene polymer is selected from poly(perfluoroethylene-perfluoroether sulfonic acid) (PTT:PFFSA).
[0038] The hole transport layer (HTL) has good film-forming properties and hole mobility, and its HOMO energy level has a good match with the work function of the HIL layer and the valence band energy level of the quantum dot light-emitting layer.
[0039] Preferably, the hole transport layer has a thickness of 10-150 nm, and the material is selected from one or more of triphenylamine-based compounds and polymer derivatives thereof, fluorene-based compounds and polymer derivatives thereof, carbazole-based compounds and polymer derivatives thereof, and spirocyclic compounds.
[0040] Furthermore, the triphenylamine compound and its derivative polymer are selected from one or more of 4,4',4"-tri(carbazole-9-yl)triphenylamine (TCTA), N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), 4,4,4"-tri[(2,3,4,5-tetraphenyl)phenyl]aniline (TTPPPA) Poly-TPD and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine (PTAA).
[0041] Furthermore, the fluorene-based compound and its derivative polymer are selected from one or more of N,N'-iminodiphenyl-4,4'-fluorene, 9,9-bis[4-(di-p-toluylamino)phenyl]-2,7-bis-(2-naphthylphenylamino)fluorene and poly(9,9-dioctylfluorene-co-N-(4-(sec-butyl)phenyl)diphenylamine) (TFB).
[0042] Furthermore, the carbazole-based compound and its derivative polymer are selected from one or more of 4,4'-bis(9-carbazole)biphenyl (CBP), 3',6'-bis(carbazole-9-yl)-bis[9-(2-ethylhexyl)carbazole-3,6-diyl] (G1CBC) and polyvinylcarbazole (PVK).
[0043] Furthermore, the spirocyclic compound is selected from one or more of N,N'-bis(3-methylphenyl)-N,N'-di(phenyl)-2,7-diamino-9,9-spirobifluorene (Spiro-TPD) and 2,2',7,7'-tetrakis(N,N-diphenylamino)-2,7-diamino-9,9-spirophenanthrene (Spiro-TAD).
[0044] The electron transport layer (ETL) has good electron mobility, electron injection performance, and is prepared by coating with a soluble solution, and the LUMO energy level must be well matched with the conduction band energy level of the light-emitting layer and the electrode work function of the cathode.
[0045] Preferably, the thickness of the electron transport layer is 10-150 nm, and the material is selected from one or more of metal oxides, imidazole compounds, pyridine compounds, pyrimidine compounds, anthracene compounds, organic metal chelates and compounds containing o-phenanthroline groups.
[0046] Furthermore, the metal oxide is selected from tin oxide (SnO2), zinc oxide (ZnO) and zinc magnesium oxide (Zn1- x Mg x O) in one or more.
[0047] Furthermore, the imidazole compound is selected from 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) and / or 1,3,5-tris(2-(pyridin-2-yl)-1H-benzo[d]imidazol-1-yl)benzene (iTPyBIB).
[0048] Furthermore, the pyridine compound is selected from 1,3,5-tris[(3-pyridyl)-3-phenyl]benzene (TmPyPB) and / or 1,3,5-tris(4-pyridin-3-ylphenyl)benzene (TpPyPB).
[0049] Furthermore, the pyrimidine compound is selected from 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PYMPM) and / or 4,6-bis(3,5-di(4-pyridyl)phenyl)-2-methylpyrimidine (B4PYMPM).
[0050] Furthermore, the anthracene compound is selected from 9,10-bis(6-phenylpyridin-3-yl)anthracene (DPPyA).
[0051] Furthermore, the organic metal chelate is selected from tris(8-hydroxyquinoline)aluminum (Alq3).
[0052] Furthermore, the compound containing o-phenanthroline group is selected from 4,7-diphenyl-1,10-phenanthroline (BPhen) and / or 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP).
[0053] The cathode of the device is highly conductive and can be used to transport charges.
[0054] Preferably, the thickness of the cathode of the device is 20-200 nm, and the material is selected from one or more of indium tin oxide (ITO), fluorine-doped tin dioxide (FTO), aluminum (Al) and silver (Ag).
[0055] The composite layer is composed of a patterned quantum dot luminescent pixel array and a barrier layer that forms a complementary pattern with the quantum dot pixels. The luminescent layer is composed of a plurality of luminescent quantum dot single-layer stacks and is embedded in the form of a pixel array between oxide nanoparticles that serve as a barrier layer insulator. Colloidal nanocrystals can be formed into luminescent quantum dot pixels at unoccupied locations of the barrier layer by solution coating after forming a patterned barrier layer. All luminescent quantum dots in the quantum dot layer have the same chemical composition, and the oxide in the barrier layer has a larger optical band gap than the quantum dots, but the surface long-chain ligands are the same or similar to the surface ligands of the quantum dots.
[0056] Preferably, the thickness of the composite layer is 10-100 nm.
[0057] Preferably, the II-VI quantum material is selected from one or more of cadmium selenide, cadmium sulfide, zinc selenide, zinc telluride and ZnCdSeS; the III-V quantum dot material is indium phosphide or indium arsenide; the perovskite semiconductor material is a quantum dot material or a bulk material, and the quantum dot material or the bulk material is selected from cesium bromide, cesium bromide, cesium chloride, methylamine bromide or methylamidinium iodide; the single mass quantum dot material is selected from one or both of carbon quantum dots and silicon quantum dots.
[0058] Specifically, the material of the light-emitting layer is one or more of II-VI quantum materials, III-V quantum materials, perovskite semiconductor materials and single-mass quantum dot materials; II-VI quantum dot materials are one or more of cadmium-based quantum dots (cadmium selenide, cadmium sulfide), zinc-based quantum dots (zinc selenide, zinc telluride), and zinc-cadmium-based alloy quantum dots (ZnCdSeS); III-V quantum dot materials are indium-based quantum dots (indium phosphide, indium arsenide); perovskite semiconductor materials are quantum dot materials or bulk materials such as cesium bromide, cesium bromide-chloride, methylamine bromide, and methylammonium iodide.
[0059] Preferably, the transfer uses a pattern stamp prepared from polydimethylsiloxane; during the transfer, the peeling speed is 1-10 mm / s and the pressure is 180-200 kPa.
[0060] Oxides have a suitable particle size, high insulation, and good film-forming properties, and there will be no self-luminescence of the barrier layer. However, since its surface usually carries hydrophilic groups such as carboxyl and hydroxyl groups, when a colloidal quantum dot solution coated with a long-chain ligand and usually dispersed in a non-polar solvent is used to form a film on the surface of a patterned oxide film layer by a solution method, it is easy to cause a serious capillary effect in the micro-nano structure of the hole array, thereby forming defects between the quantum dot luminescent pixels and the barrier layer. Therefore, improving the design of surface ligands for oxides is regarded as the key to improving the barrier layer defect problem. By coating the oxide particles with long-chain ligands (such as oleic acid, monocaprylin, oleylamine, silane long chains, etc.), non-polar solvents and common colloidal quantum dots have good wettability to them, which helps to form a conformal coating for the luminescent quantum dots. The scanning electron microscope photograph of the barrier layer of the quantum dot micro-nano pixel array formed by this scheme is shown in the figure. Figure 2 As shown, it can be seen that the quantum dots are densely embedded in the pixel pits of the barrier layer and the pixel structure is complete and clear.
[0061] Oxide nanoparticles with a particle size similar to that of luminescent quantum dots have a high specific surface area and high surface energy, which can improve their surface adhesion to the surface of polydimethylsiloxane (PDMS), the elastomeric stamp material for nanoimprinting, thereby improving the pickup rate of thin film patterns. Figure 3 As shown, it can be seen that all areas on the designed contact surface are covered with a complete oxide barrier layer and the pattern shape is clear.
[0062] The optical band gap of oxide nanoparticles is usually greater than 4eV, and they are good insulating materials. They cannot produce electrical and optical crosstalk while ensuring the patterning quality.
[0063] The present invention uses ligand exchange technology to coat oxide nanoparticles with long-chain ligands, so that the surface of the oxide nanoparticles changes from hydrophilic to lipophilic, so that the oxide nanoparticles can be formed into a film on an organic or oxide substrate by a solution coating method, and high-quality patterning can be achieved through nanoimprinting and transfer processes.
[0064] High-quality patterning, the present invention can solve the leakage current and crosstalk problems between pixels that are difficult to overcome due to the low pickup rate of the traditional barrier layer, the self-luminescence of the barrier layer, and the difficulty in wetting with the luminescent quantum dot solution.
[0065] The present invention can effectively improve the integrity of the barrier layer pattern and regulate the film thickness by accurately controlling the peeling rate and pressure during the nanoimprinting process.
[0066] The technical solution of the present invention has the following advantages over the prior art:
[0067] 1. This scheme prepares nanoparticle materials with a size similar to that of quantum dots. This material is effectively compatible with existing nanoimprint technology and achieves a high pickup rate for thin film patterns.
[0068] 2. Use insulating materials with larger band gap and no electroluminescent properties to avoid the problem of self-luminescence of the barrier layer and crosstalk between pixels;
[0069] 3. Ligand exchange is used to enable good wetting of the barrier layer surface with the quantum dot solution to prepare a densely patterned coating with conformal contact. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 The figure is a flow chart for preparing a quantum dot light-emitting diode device with a patterned barrier layer structure.
[0071] Figure 2 This is a scanning electron microscope image of the barrier layer with quantum dot micro-nano pixel array.
[0072] Figure 3 Scanning electron micrograph of the elastomer stamp surface picking up the oxide film pattern.
[0073] Figure 4 This is a comparison chart of the external quantum efficiency-brightness performance of Example 1 and Comparative Example 1.
[0074] Figure 5 This is a comparison chart of the external quantum efficiency-brightness performance of Example 2 and Comparative Example 2.
[0075] Figure 6 The emission spectra of Example 2 and Comparative Example 2 are compared.
[0076] Figure 7 This is a comparison chart of the external quantum efficiency-brightness performance of Example 3 and Comparative Example 3. DETAILED DESCRIPTION
[0077] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0078] Example 1
[0079] Preparation of InP-QDs micro-nano pixel light-emitting devices with a central wavelength of 625 nm and an oily SiO2 barrier layer
[0080] (1) Material preparation:
[0081] 1-1: Use glass cleaning liquid, deionized water, acetone and isopropyl alcohol to ultrasonically clean indium tin oxide, and then put the cleaned ITO into a UV ozone cleaning machine for 15 minutes of pretreatment;
[0082] 1-2: The silicon substrate is cleaned with UV / O3 for 40 minutes and stored in vacuum for the pre-filming of the barrier layer;
[0083] 1-3: Place the silicon wafer formed in 1-2 into a vacuum-dried reaction flask and inject anhydrous hexane under nitrogen. Then add alkylsilane to the flask and self-assemble on the silicon wafer under nitrogen for 1 hour. After completion, place the silicon wafer on a hot plate and bake at 120°C for 20 minutes to form strong covalent bonds over the entire area. Subsequently, rinse with ethanol to remove excess silane.
[0084] 1-4: Use an isopropanol dispersion of SiO2 to spin-coat on the silicon wafer formed by 1-3 and place it in a culture dish. Add perfluorotrimethoxysilane and soak for 30 seconds, then take it out and blow dry to obtain a solid-phase modified silane long-chain ligand SiO2 film for transfer printing;
[0085] 1-5: mixing and stirring a main solution of polydimethylsiloxane (PDMS) and a curing agent at a volume ratio of 10:1 to obtain a prepolymer solution;
[0086] 1-6: Place the prepolymer solution obtained in 1-5 into a vacuum dryer and evacuate to negative pressure to remove internal bubbles;
[0087] 1-7: Pour the prepolymer obtained in 1-6 into a jig with a pixel pattern template attached, and heat at 70°C for 3h;
[0088] 1-8: The cured PDMS in the jig obtained in 1-7 is cut and demolded along the pattern edge, and a portion is taken out as an elastomer stamp for nanoimprinting.
[0089] (2) Device preparation part:
[0090] 2-1: Spin coat PEDOT:PSS on ITO at a rate of 5000 rpm using a coating machine, and then anneal at 150°C to a thickness of 25 nm;
[0091] 2-2: The substrate was transferred to a glove box with a nitrogen atmosphere, and TFB was spin-coated on the substrate at a speed of 3000 rpm using a coating machine to a thickness of 30 nm, and then annealed at 150°C;
[0092] 2-3: Laminating the stamp formed by 1-8 with the silicon wafer with the spin-coated barrier layer formed by 1-4 until the pattern area is in conformal contact;
[0093] 2-4: Apply a pressure of 190 kPa on the top of the stamp in 2-3 for 10 seconds, then peel it upward at a speed of 10 mm / s to separate it from the surface of the silicon wafer and pick up the barrier film on the surface of the silicon wafer to complete its patterning;
[0094] 2-5: Align the stamp with the barrier layer pattern formed in 2-4 with the substrate obtained in 2-2 and attach them until the pattern area is in conformal contact;
[0095] 2-6: The stamp and substrate in conformal contact in 2-5 are peeled upward at a speed of 1 mm / s, so that the patterned barrier film on the surface of the stamp is released onto the substrate below;
[0096] 2-7: Spin-coat indium phosphide quantum dots (InP-QDs) on the substrate at a rate of 3000 revolutions per minute, and the thickness should be consistent with the thickness of the barrier film formed in 2-3;
[0097] 2-8: Spin-coating zinc magnesium oxide nanoparticles on the substrate at a speed of 3000 rpm to a thickness of 30 nm, and then annealing at 80° C.;
[0098] 2-9: Transfer to a vacuum evaporation device to physically vapor deposit 100 nm of silver.
[0099] FTO: device anode;
[0100] PEDOT:PSS: hole injection layer;
[0101] Pattern complementary InP-QDs and SiO2: composite layer;
[0102] ZnMgO: electron transport layer;
[0103] Ag: device cathode;
[0104] The final device structure is FTO / PEDOT:PSS / Poly-TPD / patterned complementary InP-QDs and SiO2 / ZnMgO / Ag (the order is device anode / hole injection layer / composite layer / electron transport layer / device cathode, the same below) ("patterned complementary" means that InP-QDs and SiO2 are located in the same structural layer, and the quantum dot (CdSe-QDs) micro-nano pixel array structure with a barrier layer (SiO2) described above is formed through patterning technology).
[0105] Example 2
[0106] Preparation of cadmium selenide quantum dots (CdSe-QDs) micro-nano pixel light-emitting devices with a central wavelength of 625 nm and an oily Al2O3 barrier layer
[0107] (1) Material preparation:
[0108] 1-1: Use glass cleaning liquid, deionized water, acetone and isopropanol to ultrasonically clean FTO, and then put the cleaned FTO into a UV ozone cleaning machine for 15 minutes of pretreatment;
[0109] 1-2: The silicon substrate is cleaned with UV / O3 for 40 minutes and stored in vacuum for the pre-filming of the barrier layer;
[0110] 1-3: Place the silicon wafer formed in 1-2 into a vacuum-dried reaction flask and inject anhydrous hexane under nitrogen. Then add alkylsilane to the flask and self-assemble on the silicon wafer under nitrogen for 1 hour. After completion, place the silicon wafer on a hot plate and bake at 120°C for 20 minutes to form strong covalent bonds over the entire area. Subsequently, rinse with ethanol to remove excess silane.
[0111] 1-4: Use an isopropanol dispersion of Al2O3, add oleic acid and stir for 6 hours, centrifuge the obtained suspension to obtain a precipitate. After adding n-hexane as a solvent to the precipitate, ultrasonic dispersion is performed to form an oleic acid-coated Al2O3 n-hexane dispersion;
[0112] 1-5: Mix and stir the main solution of polydimethylsiloxane and its curing agent in a volume ratio of 10:1 to obtain a prepolymer solution;
[0113] 1-6: Place the prepolymer solution obtained in 1-5 into a vacuum dryer and evacuate to negative pressure to remove internal bubbles;
[0114] 1-7: Pour the prepolymer obtained in 1-6 into a jig with a pixel pattern template attached, and heat at 70°C for 3h;
[0115] 1-8: The cured PDMS in the jig obtained in 1-7 is cut and demolded along the pattern edge, and a portion is taken out as an elastomer stamp for nanoimprinting.
[0116] (2) Device preparation part:
[0117] 2-1: Spin coat PEDOT:PSS on ITO at a rate of 5000 rpm using a coating machine, and then anneal at 150°C to a thickness of 25 nm;
[0118] 2-2: The substrate was transferred to a glove box in a nitrogen atmosphere, and the hole transport layer material Poly-TPD was spin-coated on the substrate at a rate of 3000 rpm using a coating machine to a thickness of 30 nm, and then annealed at 150°C;
[0119] 2-3: Spin-coat the dispersion formed in 1-4 onto the silicon wafer formed in 1-3 to form a barrier film
[0120] 2-4: Lay the stamp formed in 1-8 on the silicon wafer with the spin-coated barrier layer formed in 2-3 until the pattern area is in conformal contact
[0121] 2-5: Apply 190 kPa pressure to the top of the stamp in 2-4 for 10 seconds, then peel it upward at a speed of 10 mm / s to separate it from the silicon wafer surface and pick up the barrier film on the silicon wafer surface to complete its patterning
[0122] 2-6: Align the stamp with the barrier layer pattern formed in 2-5 to the substrate obtained in 2-2 and attach until the pattern area is in conformal contact.
[0123] 2-7: The stamp and substrate in conformal contact in 2-6 are peeled upward at a speed of 1 mm / s, causing the patterned barrier film on the stamp surface to be released onto the substrate below
[0124] 2-8: Spin-coat cadmium selenide quantum dots (CdSe-QDs) on the substrate at a rate of 3000 revolutions per minute, and the thickness should be consistent with the thickness of the barrier film formed in 2-3;
[0125] 2-9: Spin-coating zinc oxide nanoparticles on the substrate at a speed of 3000 rpm to a thickness of 30 nm, and then annealing at 80°C;
[0126] 2-10: Transfer to a vacuum evaporation device to physically vapor deposit 100 nm aluminum.
[0127] The final device structure is ITO / PEDOT:PSS / TFB / patterned complementary CdSe-QDs and Al2O3 / ZnO / Al.
[0128] Example 3
[0129] Preparation of cesium lead bromine perovskite quantum dots (CsPbBr3-QDs) micro-nano pixel light-emitting devices with a wavelength of 525 nm and an oily HfO2 barrier layer
[0130] 1-1: Use glass cleaning liquid, deionized water, acetone and isopropyl alcohol to ultrasonically clean indium tin oxide, and then put the cleaned ITO into a UV ozone cleaning machine for 15 minutes of pretreatment;
[0131] 1-2: The silicon substrate is cleaned with UV / O3 for 40 minutes and stored in vacuum for the pre-filming of the barrier layer;
[0132] 1-3: Place the silicon wafer formed in 1-2 into a vacuum-dried reaction flask and inject anhydrous hexane under nitrogen. Then add alkylsilane to the flask and self-assemble on the silicon wafer under nitrogen for 1 hour. After completion, place the silicon wafer on a hot plate and bake at 120°C for 20 minutes to form strong covalent bonds over the entire area. Subsequently, rinse with ethanol to remove excess silane.
[0133] 1-4: Use an isopropanol dispersion of HfO2, add oleylamine and stir for 6 hours, centrifuge the obtained suspension to obtain a precipitate. After adding n-octane as a solvent to the precipitate, ultrasonic dispersion is performed to form an oleic acid-coated HfO2 n-octane dispersion;
[0134] 1-5: Mix and stir the main solution of polydimethylsiloxane and its curing agent in a volume ratio of 10:1 to obtain a prepolymer solution;
[0135] 1-6: Place the prepolymer solution obtained in 1-5 into a vacuum dryer and evacuate to negative pressure to remove internal bubbles;
[0136] 1-7: Pour the prepolymer obtained in 1-6 into a jig with a pixel pattern template attached, and heat at 70°C for 3h;
[0137] 1-8: The cured PDMS in the jig obtained in 1-7 is cut and demolded along the pattern edge, and a portion is taken out as an elastomer stamp for nanoimprinting.
[0138] (2) Device preparation part:
[0139] 2-1: Use a coating machine to spin coat PTT:PFFSA on ITO at a rate of 5000 rpm, and then anneal at 150°C to a thickness of 25 nm;
[0140] 2-2: The substrate was transferred to a glove box in a nitrogen atmosphere, and the hole transport layer material PVK was spin-coated on the substrate at a rate of 3000 rpm using a coating machine to a thickness of 30 nm, and then annealed at 150°C;
[0141] 2-3: Spin-coat the dispersion formed in 1-4 onto the silicon wafer formed in 1-3 to form a barrier layer film;
[0142] 2-4: Laminating the stamp formed in 1-8 with the silicon wafer with the spin-coated barrier layer formed in 2-3 until the pattern area is in conformal contact;
[0143] 2-5: Apply a pressure of 190 kPa on the top of the stamp in 2-4 for 10 seconds, then peel it upward at a speed of 10 mm / s to separate it from the surface of the silicon wafer and pick up the barrier film on the surface of the silicon wafer to complete its patterning;
[0144] 2-6: Align the stamp with the barrier layer pattern formed in 2-5 with the substrate obtained in 2-2 and attach them until the pattern area is in conformal contact;
[0145] 2-7: The stamp and substrate in conformal contact in 2-6 are peeled upward at a speed of 1 mm / s, so that the patterned barrier film on the surface of the stamp is released onto the substrate below;
[0146] 2-8: Spin-coat cadmium selenide quantum dots (CdSe-QDs) on the substrate at a rate of 3000 rpm, the thickness of which should be consistent with the thickness of the barrier film formed in 2-3, and anneal at 80°C;
[0147] 2-9: Transfer to a vacuum evaporation device to physically vapor deposit a 30 nm electron transport layer of 5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi);
[0148] 2-10: Continue vapor deposition of 1 nm cathode electrode modification layer of lithium fluoride (LiF);
[0149] 2-11: Finally, a 100nm aluminum electrode is vapor deposited;
[0150] The final device structure is ITO / PTT:PFFSA / PVK / patterned complementary CsPbBr3-QDs and HfO2 / TPBi / LiF / Al.
[0151] Comparative Example 1
[0152] An indium phosphide quantum dot (InP-QDs) micro-nano pixel light-emitting device with a central wavelength of 625 nm and a PPC barrier layer was prepared.
[0153] (1) Material preparation:
[0154] 1-1: Use glass cleaning liquid, deionized water, acetone and isopropyl alcohol to ultrasonically clean indium tin oxide, and then put the cleaned ITO into a UV ozone cleaning machine for 15 minutes of pretreatment;
[0155] 1-2: The silicon substrate is cleaned with UV / O3 for 40 minutes and stored in vacuum for the pre-filming of the barrier layer;
[0156] 1-3: Place the silicon wafer formed in 1-2 into a vacuum-dried reaction flask and inject anhydrous hexane under nitrogen. Then add alkylsilane to the flask and self-assemble on the silicon wafer under nitrogen for 1 hour. After completion, place the silicon wafer on a hot plate and bake at 120°C for 20 minutes to form strong covalent bonds over the entire area. Subsequently, rinse with ethanol to remove excess silane;
[0157] 1-4: Take polypropylene carbonate (PPC) powder, add ethanol to dissolve and stir for 1 hour, and spin-coat it on the silicon wafer formed by 1-3 to obtain a PPC film for transfer;
[0158] 1-5: Mix and stir the main solution of polydimethylsiloxane and its curing agent in a volume ratio of 10:1 to obtain a prepolymer solution;
[0159] 1-6: Place the prepolymer solution obtained in 1-5 into a vacuum dryer and evacuate to negative pressure to remove internal bubbles;
[0160] 1-7: Pour the prepolymer obtained in 1-6 into a jig with a pixel pattern template attached, and heat at 70°C for 3h;
[0161] 1-8: The cured PDMS in the jig obtained in 1-7 is cut and demolded along the pattern edge, and a portion is taken out as an elastomer stamp for nanoimprinting.
[0162] (2) Device preparation part:
[0163] 2-1: Spin coat PEDOT:PSS on ITO at a rate of 5000 rpm using a coating machine, and then anneal at 150°C to a thickness of 25 nm;
[0164] 2-2: The substrate was transferred to a glove box with a nitrogen atmosphere, and TFB was spin-coated on the substrate at a speed of 3000 rpm using a coating machine to a thickness of 30 nm, and then annealed at 150°C;
[0165] 2-3: Spin-coat the dispersion formed in 1-4 onto the silicon wafer formed in 1-3 to form a barrier layer film;
[0166] 2-4: Laminating the stamp formed in 1-8 with the silicon wafer with the spin-coated barrier layer formed in 2-3 until the pattern area is in conformal contact;
[0167] 2-5: Apply a pressure of 190 kPa on the top of the stamp in 2-4 for 10 seconds, then peel it upward at a speed of 10 mm / s to separate it from the surface of the silicon wafer and pick up the barrier film on the surface of the silicon wafer to complete its patterning;
[0168] 2-6: Align the stamp with the barrier layer pattern formed in 2-5 with the substrate obtained in 2-2 and attach them until the pattern area is in conformal contact;
[0169] 2-7: The stamp and substrate in conformal contact in 2-6 are peeled upward at a speed of 1 mm / s, so that the patterned barrier film on the surface of the stamp is released onto the substrate below;
[0170] 2-8: Spin-coat indium phosphide quantum dots (InP-QDs) on the substrate at a rate of 3000 revolutions per minute, and the thickness should be consistent with the thickness of the barrier film formed in 2-3;
[0171] 2-9: Spin-coating zinc magnesium oxide nanoparticles on the substrate at a speed of 3000 rpm to a thickness of 30 nm, and then annealing at 80° C.;
[0172] 2-10: Transfer to a vacuum evaporation device to physically vapor deposit 100 nm of silver.
[0173] The final device structure is FTO / PEDOT:PSS / Poly-TPD / InP-QDs&PPC / ZnMgO / Ag.
[0174] Comparative Example 2
[0175] A cadmium selenide quantum dot (CdSe-QDs) micro-nano pixel light-emitting device with a central wavelength of 625nm and a zinc selenide / zinc sulfide quantum dot (ZnSeZnS-QDs) barrier layer was prepared.
[0176] (1) Material preparation:
[0177] 1-1: Use glass cleaning liquid, deionized water, acetone and isopropanol to ultrasonically clean FTO, and then put the cleaned FTO into a UV ozone cleaning machine for 15 minutes of pretreatment;
[0178] 1-2: The silicon substrate is cleaned with UV / O3 for 40 minutes and stored in vacuum for the pre-filming of the barrier layer;
[0179] 1-3: Place the silicon wafer formed in 1-2 into a vacuum-dried reaction flask and inject anhydrous hexane under nitrogen. Then add alkylsilane to the flask and self-assemble on the silicon wafer under nitrogen for 1 hour. After completion, place the silicon wafer on a hot plate and bake at 120°C for 20 minutes to form strong covalent bonds over the entire area. Subsequently, rinse with ethanol to remove excess silane.
[0180] 1-4: Using zinc selenide / zinc sulfide quantum dots (ZnSeZnS-QDs) solution as the barrier layer material;
[0181] 1-5: Mix and stir the main solution of polydimethylsiloxane and its curing agent in a volume ratio of 10:1 to obtain a prepolymer solution;
[0182] 1-6: Place the prepolymer solution obtained in 1-5 into a vacuum dryer and evacuate to negative pressure to remove internal bubbles;
[0183] 1-7: Pour the prepolymer obtained in 1-6 into a jig with a pixel pattern template attached, and heat at 70°C for 3h;
[0184] 1-8: The cured PDMS in the jig obtained in 1-7 is cut and demolded along the pattern edge, and a portion is taken out as an elastomer stamp for nanoimprinting.
[0185] (2) Device preparation part:
[0186] 2-1: Spin coat PEDOT:PSS on ITO at a rate of 5000 rpm using a coating machine, and then anneal at 150°C to a thickness of 25 nm;
[0187] 2-2: The substrate was transferred to a glove box in a nitrogen atmosphere, and the hole transport layer material Poly-TPD was spin-coated on the substrate at a rate of 3000 rpm using a coating machine to a thickness of 30 nm, and then annealed at 150°C;
[0188] 2-3: Spin-coat the zinc selenide / zinc sulfide quantum dots (ZnSeZnS-QDs) solution prepared in 1-4 onto the silicon wafer formed in 1-3 to form a barrier layer film;
[0189] 2-4: Laminating the stamp formed in 1-8 with the silicon wafer with the spin-coated barrier layer formed in 2-3 until the pattern area is in conformal contact;
[0190] 2-5: Apply a pressure of 190 kPa on the top of the stamp in 2-4 for 10 seconds, then peel it upward at a speed of 10 mm / s to separate it from the surface of the silicon wafer and pick up the barrier film on the surface of the silicon wafer to complete its patterning;
[0191] 2-6: Align the stamp with the barrier layer pattern formed in 2-5 with the substrate obtained in 2-2 and attach them until the pattern area is in conformal contact;
[0192] 2-7: The stamp and substrate in conformal contact in 2-6 are peeled upward at a speed of 1 mm / s, so that the patterned barrier film on the surface of the stamp is released onto the substrate below;
[0193] 2-8: Spin-coat cadmium selenide quantum dots (CdSe-QDs) on the substrate at a rate of 3000 revolutions per minute, and the thickness should be consistent with the thickness of the barrier film formed in 2-3;
[0194] 2-9: Spin-coating zinc oxide nanoparticles on the substrate at a speed of 3000 rpm to a thickness of 30 nm, and then annealing at 80°C;
[0195] 2-10 The sample was transferred to a vacuum evaporation device and 100 nm aluminum was physically vapor deposited.
[0196] The final device structure is ITO / PEDOT:PSS / TFB / CdSe-QDs&ZnSeZnS-QDs / ZnO / Al.
[0197] Comparative Example 3
[0198] Preparation of Cesium Lead Bromide Perovskite Quantum Dots (CsPbBr3-QDs) Micro-Nano Pixel Light-Emitting Device with a Central Wavelength of 525nm and an Unmodified Al2O3 Barrier Layer
[0199] Preparation of cesium lead bromine perovskite quantum dots (CsPbBr3-QDs) micro-nano pixel light-emitting devices with a wavelength of 525 nm and an oily HfO2 barrier layer
[0200] 1-1: Use glass cleaning liquid, deionized water, acetone and isopropyl alcohol to ultrasonically clean indium tin oxide, and then put the cleaned ITO into a UV ozone cleaning machine for 15 minutes of pretreatment;
[0201] 1-2: The silicon substrate is cleaned with UV / O3 for 40 minutes and stored in vacuum for the pre-filming of the barrier layer;
[0202] 1-3: Place the silicon wafer formed in 1-2 into a vacuum-dried reaction flask and inject anhydrous hexane under nitrogen. Then add alkylsilane to the flask and self-assemble on the silicon wafer under nitrogen for 1 hour. After completion, place the silicon wafer on a hot plate and bake at 120°C for 20 minutes to form strong covalent bonds over the entire area. Subsequently, rinse with ethanol to remove excess silane.
[0203] 1-4: Using Al2O3 isopropanol dispersion as the barrier material;
[0204] 1-5: Mix and stir the main solution of polydimethylsiloxane and its curing agent in a volume ratio of 10:1 to obtain a prepolymer solution;
[0205] 1-6: Place the prepolymer solution obtained in 1-5 into a vacuum dryer and evacuate to negative pressure to remove internal bubbles;
[0206] 1-7: Pour the prepolymer obtained in 1-6 into a jig with a pixel pattern template attached, and heat at 70°C for 3h;
[0207] 1-8: The cured PDMS in the jig obtained in 1-7 is cut and demolded along the pattern edge, and a portion is taken out as an elastomer stamp for nanoimprinting.
[0208] (2) Device preparation part:
[0209] 2-1: Use a coating machine to spin coat PTT:PFFSA on ITO at a rate of 5000 rpm, and then anneal at 150°C to a thickness of 25 nm;
[0210] 2-2: The substrate was transferred to a glove box with a nitrogen atmosphere, and a hole transport layer material poly(N-vinyl carbazole) (PVK) was spin-coated on the substrate at a rate of 3000 rpm using a coating machine to a thickness of 30 nm, and then annealed at 150°C;
[0211] 2-3: Spin-coat the isopropanol dispersion of Al2O3 prepared in 1-4 onto the silicon wafer formed in 1-3 to form a barrier film;
[0212] 2-4: Laminating the stamp formed in 1-8 with the silicon wafer with the spin-coated barrier layer formed in 2-3 until the pattern area is in conformal contact;
[0213] 2-5: Apply a pressure of 190 kPa on the top of the stamp in 2-4 for 10 seconds, then peel it upward at a speed of 10 mm / s to separate it from the surface of the silicon wafer and pick up the barrier film on the surface of the silicon wafer to complete its patterning;
[0214] 2-6: Align the stamp with the barrier layer pattern formed in 2-5 with the substrate obtained in 2-2 and attach them until the pattern area is in conformal contact;
[0215] 2-7: The stamp and substrate in conformal contact in 2-6 are peeled upward at a speed of 1 mm / s, causing the patterned barrier film on the stamp surface to be released onto the substrate below
[0216] 2-8: Spin-coat cadmium selenide quantum dots (CdSe-QDs) on the substrate at a rate of 3000 rpm, the thickness of which should be consistent with the thickness of the barrier film formed in 2-3, and anneal at 80°C;
[0217] 2-9: Transfer to a vacuum evaporation device to physically vapor deposit a 30 nm electron transport layer of 5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi);
[0218] 2-10: Continue vapor deposition of 1 nm cathode electrode modification layer of lithium fluoride (LiF);
[0219] 2-11: Finally, a 100nm aluminum electrode is vapor deposited;
[0220] The final device structure is ITO / PTT:PFFSA / PVK / CsPbBr3-QDs&SiO2 / TPBi / LiF / Al.
[0221] Effect evaluation 1
[0222] (1) The devices in Example 1 and Comparative Example 1 were placed in a test fixture with a silicon tube, and a Keithley 2400 source meter was used to output the voltage and record the current density. A picoammeter Keithley 6485 was used to measure the silicon tube response current, and the corresponding current efficiency, external quantum efficiency (EQE) and brightness were calculated. Figure 4 As shown, the high integrity of the blocking layer pattern effectively increases the light-emitting area, thereby improving the device EQE, proving that the modified oxide patterned blocking layer effectively improves the pickup rate of the blocking layer film, thereby improving the integrity of the blocking layer pattern.
[0223] (2) The devices in Example 2 and Comparative Example 2 were placed in a test fixture with a silicon tube, and a Keithley 2400 source meter was used to output the voltage and record the current density. A picoammeter Keithley 6485 was used to measure the silicon tube response current, and the corresponding current density, luminous efficiency (EQE) and brightness were calculated. Figure 5 As shown in (Performance Comparison), the high insulation of the barrier layer material effectively reduces the device leakage current, thereby improving the device EQE. Figure 6 As shown, the oxide barrier layer material itself does not emit light, so the luminescence peak of the blue light quantum dot barrier layer in Comparative Example 2 does not appear, and the crosstalk between pixels is effectively reduced.
[0224] (3) The devices in Example 3 and Comparative Example 3 were placed in a test fixture with a silicon tube, and a Keithley 2400 source meter was used to output the voltage and record the current density. A picoammeter Keithley 6485 was used to measure the silicon tube response current, and the corresponding current density, luminous efficiency (EQE) and brightness were calculated. Figure 7As shown, the high integrity of the blocking layer pattern effectively improves the filling quality of the pixel in the blocking layer, thereby improving the device EQE, proving that the modified oxide patterned blocking layer effectively improves the wettability of the blocking layer with the colloidal quantum dot solution, thereby reducing the light-emitting layer defects of the cesium lead bromine perovskite quantum dot patterned light-emitting device.
[0225] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A quantum dot light-emitting diode device with a patterned barrier layer structure, characterized in that: It includes a device anode, a hole injection layer, a hole transport layer, a composite layer, an electron transport layer and a device cathode which are arranged in sequence; The composite layer is composed of a patterned barrier layer and a light-emitting layer; the light-emitting layer is filled in the pattern gaps of the barrier layer in the form of a pixel array; The material of the light-emitting layer is selected from one or more of II-VI quantum materials, III-V quantum materials, perovskite semiconductor materials and single-mass quantum dot materials; The barrier layer is obtained by transferring a barrier material, and the barrier material is prepared by a solid phase modification or ligand exchange method; The solid phase modification method is to apply the isopropanol dispersion containing the oxide on the reaction silicon wafer, add perfluorotrimethoxysilane to soak for 20-40 seconds and then dry; the ligand exchange method is to mix the isopropanol dispersion containing the oxide and the ligand for 5-7 hours and then separate, disperse the separated precipitate in n-hexane and then apply it on the reaction silicon wafer; the oxide is selected from inorganic non-metallic oxides and metal oxides; the inorganic non-metallic oxide is SiO2 nanoparticles, and the metal oxide is nanoparticles selected from HfO2, Al2O3, Ta2O5 or ZrO2; the ligand is selected from one or more of oleic acid, oleylamine, silane and octadecyl mercaptan; The reaction silicon wafer is obtained by placing the silicon wafer and alkylsilane in hexane under a protective atmosphere, reacting for 1-2 hours, and then baking at 110-130° C. for 15-25 minutes.
2. The quantum dot light-emitting diode device with a patterned barrier layer structure as claimed in claim 1, characterized in that: The thickness of the device anode is 20-200 nm, and the material is selected from one or more of indium tin oxide, fluorine-doped tin dioxide, aluminum and silver.
3. The quantum dot light-emitting diode device with a patterned barrier layer structure as claimed in claim 1, characterized in that: The hole injection layer has a thickness of 10-150 nm, and its material is selected from one or both of polyethylene polymers and polythiophene polymers.
4. The quantum dot light-emitting diode device with a patterned barrier layer structure as claimed in claim 1, characterized in that: The hole transport layer has a thickness of 10-150 nm, and the material is selected from one or more of triphenylamine-based compounds and polymer derivatives thereof, fluorene-based compounds and polymer derivatives thereof, carbazole-based compounds and polymer derivatives thereof, and spirocyclic compounds.
5. The quantum dot light-emitting diode device with a patterned barrier layer structure as claimed in claim 1, characterized in that: The thickness of the electron transport layer is 10-150 nm, and the material is selected from one or more of metal oxides, imidazole compounds, pyridine compounds, pyrimidine compounds, anthracene compounds, organic metal chelates and compounds containing o-phenanthroline groups.
6. The quantum dot light-emitting diode device with a patterned barrier layer structure as claimed in claim 1, characterized in that: The thickness of the cathode of the device is 20-200 nm, and the material is selected from one or more of indium tin oxide, fluorine-doped tin dioxide, aluminum and silver.
7. The quantum dot light-emitting diode device with a patterned barrier layer structure as claimed in claim 1, characterized in that: The thickness of the composite layer is 10-100 nm.
8. The quantum dot light-emitting diode device with a patterned barrier layer structure as claimed in claim 1, characterized in that: The II-VI quantum material is selected from one or more of cadmium selenide, cadmium sulfide, zinc selenide, zinc telluride and ZnCdSeS; the III-V quantum dot material is indium phosphide or indium arsenide; the perovskite semiconductor material is a quantum dot material or a bulk material, and the quantum dot material or the bulk material is selected from cesium bromide, cesium bromide, cesium chloride, methylamine bromide or methylamidinium iodide; the single mass quantum dot material is selected from one or both of carbon quantum dots and silicon quantum dots.
9. The quantum dot light-emitting diode device with a patterned barrier layer structure as claimed in claim 1, characterized in that: The transfer uses a pattern stamp prepared with polydimethylsiloxane.
10. The quantum dot light-emitting diode device with a patterned barrier layer structure as claimed in claim 1, characterized in that: During the transfer, the peeling speed is 1-10 mm / s and the pressure is 180-200 kPa.
Citation Information
Patent Citations
Display substrate and preparation method thereof, and display device
CN106784366A
Quantum dot light emitting diode and preparation method thereof
CN114695745A
Display device and electronic apparatus
JP2017162832A
Light emitting device and method for manufacturing light emitting device
US20220328779A1